Advances in Practical Applications of Agents, Multi-Agent Systems, and Complex Systems Simulation. the PAAMS Collection: 20th International Conference, PAAMS 2022, l'Aquila, Italy, July 13-15, 2022, Proceedings - Dignum, Frank; Mathieu, Philippe; Corchado, Juan Manuel; De La Prieta, Fernando (Lecture Notes in Computer Science, 2022)
This book constitutes the proceedings of the 20th International Conference on Practical Applications of Agents and Multi-Agent Systems, PAAMS 2022, held in L'Aquila, Italy in July 2022.The 37 full papers in this book were reviewed and selected from 67 submissions. Another 10 demonstrations papers were selected from 11 submissions are presented here as short papers. The papers deal with the application and validation of agent-based models, methods, and technologies in a number of key applications areas, including: advanced models and learning, agent-based programming, decision-making, education and social interactions, formal and theoretic models, health and safety, mobility and the city, swarms and task allocation.